Should states allow early school enrollment? An analysis of individuals' long-term labor market effects - Katja Görlitz; Pascal Heß; Marcus Tamm (Empirical Economics, 2025)
This study provides a policy evaluation of laws allowing early school enrollment of children, i.e., enrollment before the official school starting age. It investigates the effects of early enrollment on educational attainment, wages and employment. While the school starting age is usually determined by children's date of birth and legal cutoffs, some German states allowed early enrollment in some years. Exploiting state and cohort variation, the results show that male early enrollees attain fewer years of schooling, enter the labor market earlier and have a larger labor market attachment at around age 16. Positive wage effects persist until approximately age 35. Results for women roughly resemble those for men, but they are less convincingly estimated.
Keywords: I28; J21; J24; 330; Early enrollment policy; Early school entry; Wages; Employment; School starting age